Direction of Apparent Motion During Smooth Pursuit Is Determined Using a Mixture of Retinal and Objective Proximities. (June 2020) - Terao, Masahiko; Nishida, Shin'ya
Many studies have investigated various effects of smooth pursuit on visual motion processing, especially the effects related to the additional retinal shifts produced by eye movement. In this article, we show that the perception of apparent motion during smooth pursuit is determined by the interelement proximity in retinal coordinates and also by the proximity in objective world coordinates. In Experiment 1, we investigated the perceived direction of the two-frame apparent motion of a square-wave grating with various displacement sizes under fixation and pursuit viewing conditions. The retinal and objective displacements between the two frames agreed with each other under the fixation condition. However, the displacements differed by 180 degrees in terms of phase shift, under the pursuit condition. The proportions of the reported motion direction between the two viewing conditions did not coincide when they were plotted as a function of either the retinal displacement or of the objective displacement; however, they did coincide when plotted as a function of a mixture of the two. The result from Experiment 2 showed that the perceived jump size of the apparent motion was also dependent on both retinal and objective displacements. Our findings suggest that the detection of the apparent motion during smooth pursuit considers the retinal proximity and also the objective proximity. This mechanism may assist with the selection of a motion path that is more likely to occur in the real world and, therefore, be useful for ensuring perceptual stability during smooth pursuit.